Insecticide Activity of Cerbera manghas Fruit Exstract to Sitophilus oryzae (Coleoptera: Curculionidae) - Ikhsan Guswenrivo; Didi Tarmadi; Sulaeman Yusuf (Jurnal Ilmu dan Teknologi Kayu Tropis, 2013)
It was informed that the fruit extract of Cerbera manghas has antitermic and bio-larvicidal activities. The objective of this research is to study the effect of Cebera manghas fruit extracts on the mortality of Sitophilus oryzae (Coleoptera: Curculionidae). Dried sample of C. manghas fruit was milled and then extracted with maceration method using methanol. Crude extract was then dried and fractioned into 2 fractions i.e. n-Hexane and ethyl acetate. Three concentration of extracts (i.e. 3, 5, and 7.5%) were applied for bioassay test in the difference baited time (i.e. 30 min, 1 h, and 3 h). The results indicated that n-hexane fraction of C. manghas fruit extract was the most active fraction and it was indicated by the highest mortality of S. oryzae at all concentration. The longer the baited time resulted the higher the mortality of S. oryzae.Key words: bio-assay, Cerbera manghas, extractive, insecticide activity, Sitophilus oryzae